Guides of the Atlas An Ethnography of Publicness, Transnational Cooperation and Mountain Tourism in Morocco - Holdermann, Simon (Media in Action, 2023)
How do digital media technologies shape or restructure social practice? And which transitions and demarcations of different forms of publicness arise in this context? Simon Holdermann examines this question in his ethnography of everyday life in the High Atlas Mountains of Morocco. In order to approach the ongoing, historically situated social transformations of the region, he analyses a variety of media practices concerning the organizational work and transnational cooperation that take place there - in particular at the intersection of mountain tourism, NGO work, and local self-government.